(Hf0.5Ta0.5)C ultra-high temperature ceramic solid solution nanowires. (1st June 2023) - Chen, Hui; Zhang, Yulei; Fu, Yanqin; Meng, Jiachen; Miao, Qing; Zhang, Jianhua; Li, Hejun
Highlights: A novel (Hf0.5 Ta0.5 )C solid solution nanowire, which combines the perfect properties of bulk materials and unique geometry properties of 1D nanostructures. The indispensable role of catalyst in formation and growth of solid solution nanowires. The nanowires exhibit excellent high-temperature stability at 1900 °C and maintain 1D nano-structures at the oxyacetylene scouring and ablation at 2300 °C. The internal structure and element distribution of nanowires remain unchanged at high temperature even if the surface atoms are rearranged. Abstract: Ultra-high temperature ceramic (UHTC) nanowires are potential reinforcement materials due to it combines the perfect properties of bulk materials and unique geometric properties of one-dimensional (1D) nanostructures. Thus, developing 1D nanomaterials that have excellent morphology and structure retention in ultra-high temperature environments is of prime importance to bring their outstanding performance into full play. Herein, we report the novel solid solution ((Hf0.5 Ta0.5 )C) ceramic nanowires, which could not only maintain morphological and structural stability at 1900 °C but also exhibit 1D nanostructures under oxyacetylene scouring and ablation at 2300 °C. The morphology evolution of nanowires obeys the Rayleigh instability mechanism, and the internal structure and element distribution of nanowires remain unchanged even if the surface atoms are rearranged. The fascinating nanowires are demonstrated to have great potential as ideal reinforcement materials of composite materials and toughening phases of ceramics that are applied in ultra-high temperature environments, as well as excellent performance enhancement phases of functional materials. Our work may provide new insights into the development of ceramic nanowires and widen their applications.